PRINCIPLES OF PUBLIC RELATIONS IN LEADERSHIP IN EDUCATIONAL INSTITUTIONS - Hamdi, Liwaul; Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public Relations (PR) in educational institutions plays an important role in building a positive image, strengthening relationships with the community, and supporting educational goals. PR serves as a communication bridge between educational institutions and external and internal parties, including parents, the community, and the government. With the principles of openness, clarity of communication, and collaboration, PR helps improve the quality of education and create more inclusive and responsive relationships to developments in the era. This study uses a library method to analyze theories, concepts, and research results related to the role of public relations in educational leadership. Researchers collect literature on public relations, educational leadership, and case studies of its application. The aim is to understand how public relations improves communication, image management, and transparency in internal-external relations of educational institutions, as well as the challenges faced by educational leaders. This study identifies the principles of public relations communication in educational leadership, including openness, accommodation, negotiation, proactivity, and partnership. The findings show that principals actively apply these principles, building effective relationships with internal and external stakeholders. The application of these principles increases trust, accountability, and quality of education and creates beneficial collaboration in achieving educational goals. This study shows that the application of public relations communication principles in educational leadership has a significant impact on managerial effectiveness and goal achievement. Three main principles: openness, accommodation and negotiation, and proactivity help build effective communication between leaders and stakeholders. Suggestions include developing communication skills, increasing transparency, and strengthening partnerships with external parties to create an inclusive and supportive educational environment.